Pocahontas and the strangers - Bulla, Clyde Robert; Burchard, Peter (New York : Scholastic Book Services, Crowell, 1971)
A fictionalized account of the life of Pocahontas woven about the few facts known from historical records.
Keywords: Pocahontas, -- -1617 -- Juvenile fiction